THE EFFECT OF ORALLY ADMINISTERED CATFISH (Clarias gariepinus) SKIN AND MEAT ON EPITHELIALIZATION THICKNESS AND COLLAGEN DENSITY IN INCISION WOUND OF WISTAR RAT (Rattus norvegicus) - Muhammad Irsyad Baihaqi; Muhammad Duddy Satrianugraha; Tiar M Pratamawati; Donny Nauphar (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Alternative medicine using animal is still rare whereas Indonesia have a lot of potential natural resources. Catfish is easily found animal in Indonesia and is common consumed as nutriment sources contains albumin, amino acid and fatty acids which plays an essential role of wound healing process. This study will determine effect of orally administered catfish (Clarias gariepinus) skin and meat on epithelialization thickness and collagen density in incision wound of white male rat (Rattus norvegicus).Methods: This experimental post-test only group design used 30 white male rat (Rattus norvegicus), that randomly divided into 4 tratment goup and one control group. The treatment group was given 12,5 mg/g W, 25 mg/g W, 37,5 mg/g W and 50 mg/g W dose of catfish (Clarias gariepinus) skin and meat flour, in the other hand the contol group were given aquades. Non-parametric analyses using Kruscall-Wallis and Mann Whitney test were used to compare epithelization thickness and collagen density.Result: The comparison results of epithelialization thickness between group C with TGI, C with TG2, C with TG3 and C with TG4 showed significant differences (p<0.05). TG4 was the thickest of all groups. Significant differences were also observed in collagen density result between C with TGI, C with TG2, C with TG3 and C with TG4 (p <0,05) TG4 showed the highest density of all groups.Conclusion: Catfish (Clarias gariepinus) skin and meat flour with 50 mg/200g W dose is effective for wound healing and increasing epithelial thickness and collagen density in Wistar rat (Rattus norvegicus) incision wounds.